2013
DOI: 10.1021/jp405591j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformations and Absorption Properties of Crystalline 7-Amino-6-nitrobenzodifuroxan under High Pressures

Abstract: The structural, electronic, and absorption properties of crystalline 7-amino-6-nitrobenzodifuroxan (ANBDF) under hydrostatic compression of 0–110 GPa have been studied by using DFT calculations. Our results show that there three structural transformations occurred at the pressure of 35, 70, and 100 GPa. The first structural transformation makes the positions of the molecules in the crystal rearranged and obviously improves the planarity. The second one forms a new C7–O10 covalent bond and transforms a boat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
2
23
1
Order By: Relevance
“…Brillouin zone sampling was obtained using Monkhorst–Pack grids 2 × 5 × 5 for all simulations. The Broyden, Fletcher, Goldfarb, and Shannon (BFGS) method were used to relax the structures, allowing both atomic positions and lattice parameters to optimize, with space group symmetry constrained, simultaneously . Here convergence criteria were applied: maximum change in system energy = 1 × 10 −5 eV, maximum root‐mean‐square (RMS) force = 0.003 eV Å −1 , maximum RMS stress = 0.01 GPa, maximum RMS displacement = 0.001 Å. Single‐point energy (SPE) calculation method in CASTEP were further performed on the structures that previously optimized in order to determine final energy.…”
Section: Methodsmentioning
confidence: 99%
“…Brillouin zone sampling was obtained using Monkhorst–Pack grids 2 × 5 × 5 for all simulations. The Broyden, Fletcher, Goldfarb, and Shannon (BFGS) method were used to relax the structures, allowing both atomic positions and lattice parameters to optimize, with space group symmetry constrained, simultaneously . Here convergence criteria were applied: maximum change in system energy = 1 × 10 −5 eV, maximum root‐mean‐square (RMS) force = 0.003 eV Å −1 , maximum RMS stress = 0.01 GPa, maximum RMS displacement = 0.001 Å. Single‐point energy (SPE) calculation method in CASTEP were further performed on the structures that previously optimized in order to determine final energy.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies[20][21][22][23][24][33][34][35] have reported that the external pressure can induce the changes of molecular Struct Chem…”
mentioning
confidence: 99%
“…Brillouin zones sampling was performed using the Monkhost‐Pack scheme with a k‐point grid of 1 × 1 × 1. The values of the kinetic energy cutoff and the k‐point grid were determined to ensure the convergence of total energies …”
Section: Methodsmentioning
confidence: 99%